2018
DOI: 10.1001/jamafacial.2018.0230
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of a Volumizing Hyaluronic Acid Filler for Treatment of Infraorbital Hollows

Abstract: IMPORTANCE Hyaluronic acid filler can be safely used as a soft-tissue filler for correction of infraorbital hollowing. It has a high overall patient satisfaction profile among patients. OBJECTIVE To report safety and patient satisfaction outcomes of Juvéderm Voluma XC for correction of infraorbital hollows. DESIGN, SETTING, AND PATIENTSThis was a retrospective observational study performed at a private ambulatory facial plastic and reconstructive surgery practice. Participants were all patients 21 to 85 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 21 publications
0
49
0
1
Order By: Relevance
“…This is the first analysis using a validated PRO instrument, the FACE‐Q, in a clinical study of the safety and effectiveness of an injectable HA filler for the treatment of fine lines and improvements in attributes of skin quality. FACE‐Q improvements in studies of injectable HA fillers have been shown previously; however, these studies either included a combination of treatments or involved injections in limited regions of the face . This prospective study in 131 subjects demonstrated that injections of VYC‐12 in the full face, with optional treatment in the neck, yielded significant improvements in PRO measures.…”
Section: Discussionmentioning
confidence: 63%
“…This is the first analysis using a validated PRO instrument, the FACE‐Q, in a clinical study of the safety and effectiveness of an injectable HA filler for the treatment of fine lines and improvements in attributes of skin quality. FACE‐Q improvements in studies of injectable HA fillers have been shown previously; however, these studies either included a combination of treatments or involved injections in limited regions of the face . This prospective study in 131 subjects demonstrated that injections of VYC‐12 in the full face, with optional treatment in the neck, yielded significant improvements in PRO measures.…”
Section: Discussionmentioning
confidence: 63%
“…The reported follow-up duration, when mentioned, ranged from 12 months [29] to 5 years [39,69] , with prolonged edema, the Tyndall effect and contour irregularities as the most commonly reported complications, along with diplopia [25] , and xanthelasma-like reactions [53] as a rare occurrence. Complications were also reported in several articles, even if not the focus of the study [13,17,22,28,32,[71][72][73][74][75] , and included two cases of cellulitis and one of migraine [13] .…”
Section: Complicationsmentioning
confidence: 99%
“…Research focused on personal techniques purposed by the authors have been published since 2005. Airan and Born [11] and Kane [12] wrote the first articles ever about this topic, both in 2005; technique refinement and new trends have been published in 2006 [22,23] , 2007 [24,33] , 2011 [16,32,76] , 2012 [26,41,42,66] , 2013 [73] , 2014 [43] , 2015 [48][49][50] , 2016 [27,28] , 2017 [17,52] , 2018 [19,71,74] and 2019 [21] .…”
Section: Techniquementioning
confidence: 99%
“…Figure B shows that a typical Tyndall effect can be seen for the samples with chitosan/citric acid mass ratios from 1:2 to 1:6, where a laser beam passes through the colloidal chitosan solution leaving a clear track due to light scattering. However, the sample with a 1:1 mass ratio has no significant Tyndall effect, which can be attributed to the large size fragments, due to the insufficient degree of hydrolysis when the acid concentration was too low . The large chitosan fragmentation hinders the further formation of an integral 3D chitosan network .…”
mentioning
confidence: 99%
“…However, the sample with a 1:1 mass ratio has no significant Tyndall effect, which can be attributed to the large size fragments, due to the insufficient degree of hydrolysis when the acid concentration was too low. 69 The large chitosan fragmentation hinders the further formation of an integral 3D chitosan network. 70 Consequently, the mass ratios between chitosan and citric acid from 1:2 to 1:6 (marked as CC-1, CC-2, CC-3, CC-4, and CC-5, respectively) are selected for the formation of chitosan film in the following device fabrication.…”
mentioning
confidence: 99%